La extensión agrícola y la asistencia técnica en el control de malezas en Colombia - Doll, Jerry D. (1974)
Some of the differences and similarities between the extension service agronomists and those of technical assistance were compared. Important differences in percent of time dedicated to weed control, sources of information and the importance that the farmers of each group assign to weed control were observed. The extensionist carriers out various weed control activities. There should be more cooperation between the researchers and the herbicide industry with the extensionist. The technical assistance personnel dedicate more time to weed control and their farmers believe weed control is more important than do those of the extension service